2010
DOI: 10.1007/s10344-010-0420-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects on brown bear (Ursus arctos) spermatozoa freezability of different extender and dilution ratios used for pre-freezing centrifugation

Abstract: The objective of this study was to determine how the extender and dilution ratio used during centrifugation affect bear spermatozoa quality before and after freezingthawing. Semen was collected from 15 brown bears by electroejaculation. In experiment 1, semen was divided into five aliquots and diluted using one of the following extenders: Tris-citric-glucose (TCG), Tris-citric-glucose-3% BSA, Tris-citric-glucose-1% egg yolk or CaninePro. In experiment 2, semen was divided into five aliquots and diluted 1:1, 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Centrifugation is a necessary step to increase the concentration of brown bear semen obtained by electroejaculation and particularly in urospermic ejaculates that usually have lesser cell concentrations. Previous studies assessing the deleterious effects of centrifugation indicated that it is not a harmful procedure for brown bear spermatozoa (Nicolas et al, 2011;2012a). In the present study, the Control sample treated only with centrifugation was amongst those with the most desirable values for sperm motility, viability and acrosomal status, and the toxic effect of urine was not evident.…”
Section: Tm (%) Pm (%) Vap (M/s) Lin (%) Dacro Viabmentioning
confidence: 76%
See 2 more Smart Citations
“…Centrifugation is a necessary step to increase the concentration of brown bear semen obtained by electroejaculation and particularly in urospermic ejaculates that usually have lesser cell concentrations. Previous studies assessing the deleterious effects of centrifugation indicated that it is not a harmful procedure for brown bear spermatozoa (Nicolas et al, 2011;2012a). In the present study, the Control sample treated only with centrifugation was amongst those with the most desirable values for sperm motility, viability and acrosomal status, and the toxic effect of urine was not evident.…”
Section: Tm (%) Pm (%) Vap (M/s) Lin (%) Dacro Viabmentioning
confidence: 76%
“…Immediately after collection, fresh semen was divided into six aliquots; five were diluted with each previously described washing extender (1 fresh semen: 2 extender, v/v) and centrifuged at 600 × g for 6 min (Nicolas et al, 2011); and the other was centrifuged without dilution and was used as the Control. After centrifugation, the supernatant was removed and the pellet was re-suspended in TTF-ULE extender at 20-22 • C and cryopreserved (Section 2.4).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of centrifugation on spermatozoa may be influenced by many factors, such as centrifugation time, centrifugal forces, dilution rate, semen extender and individual variability. Several authors working (Okano et al 2006), 200×g for 8 min (Spindler et al 2004), and we have used 600×g for 6 min (Nicolas et al 2011). A variety of centrifugation regimes for dog has been reported: 400×g for 5 min (Kawakami et al 2002), 700×g for 5 min (Schafer-Somi et al 2006), 700×g for 10 min (Okano et al 2004a), and 700×g for 6 min (Rota et al 1995).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, for the ejaculates of some species, centrifugation of semen before cryopreservation is necessary to reach an appropriate cellular concentration (dog [12], stallion [13,14], and brown bear [2,6]) or even to remove seminal plasma (goat [15]) and clean urinecontaminated samples (horse [16] and brown bear [17]). Despite previous studies assessing the deleterious effects of centrifugation, this procedure does not appear to be harmful for brown bear spermatozoa [18,19]. Regarding seminal plasma, some studies have shown beneficial effects of its addition during semen processing and cryopreservation (deer [20] and ram [21]), whereas other authors have reported deleterious effects (dog [12], goat [22], ram [23], stallion [13,14], and bull [24]).…”
Section: Introductionmentioning
confidence: 97%